Using irrigation to kick‐start multiple‐use water services for small‐scale farmers in Malawi: A case study of the Nkhata Bay District†. (16th September 2018) - Stedman, Sam; Mnyimbiri, Alien Mathews; Kawonga, Zinyengo; Malota, Mphatso; Njera, Dalo; Hall, Ralph P.; Holm, Rochelle H.
Abstract: Irrigation schemes are an important part of meeting the national agenda in Malawi, yet the design and management of these schemes have not taken advantage of emerging approaches that could improve their performance. One such idea is the concept of multiple‐use water services (MUS). This case study focuses on rural irrigation systems in the Nkhata Bay District, evaluating system usage, profiles of the irrigators, and barriers to irrigation to identify opportunities to kick‐start MUS using existing organizational structures. Interviews were conducted with 141 respondents from 5 functioning irrigation sections. The study found that there are already systems in place for cooperation, with both the government and communities each contributing to long‐term sustainability. Basic MUS could advance the water–energy–food–health nexus and build more resilient communities. The following recommendations would enable communities and development partners to advance irrigation‐based MUS in Malawi: (i) target long‐established, committed, farmer groups; (ii) provide reliable and sustainable local technologies to lift water; (iii) improve access to markets and inputs to support higher‐value cash crops being grown on irrigated land; (iv) create an overlap between community‐level irrigation and borehole committees, private sectors, local government ministries and development partners. © 2018 John Wiley & Sons, Ltd.